Re-use potential of carbon fibre fabric recovered from infusible thermoplastic CFRPs in 2nd generation thermosetting-matrix composites. (December 2021) - Gebhardt, Magnus; Manolakis, Ioannis; Kalinka, Gerhard; Deubener, Joachim; Chakraborty, Souvik; Meiners, Dieter
Abstract: The research presented here attempts to assess the potential for re-using carbon fibre (CF) fabrics recovered from recycling infusible acrylic thermoplastic carbon fibre reinforced polymer composites (CFRPs) in a universal manner, i.e. by combining with a wide variety of matrices to manufacture 2nd generation composite laminates by resin infusion. The 2nd generation composites have been compared in terms of bulk and interfacial properties against counteparts processed with virgin carbon fibre fabric infused with the same matrices. Generally, an increase in damping (tanδ) was observed in all 2nd generation composites, which can be attributed to a residual thin thermoplastic layer present on the recovered fibres. The interfacial adhesion of the 2nd generation composites was investigated by shear tests and scanning electron micsoscopy, and also appears to be less influenced by the type of matrix. Graphical abstract: Image 1 Highlights: Recycling of CFRPs 2nd Generation re-use of reclaimed carbon fibres A universal re-use potential of the reclaimed carbon fibres Shear strenght of reclaimed carbon fibres using single fibre push-out test Fractorgraphy for interfacial adhesion of the reclaimed carbon fibres